The SPORT report : making REACH work in practice - Ahrens, Andreas; Jepsen, Dirk; Heitmann, Kerstin; Claus, Frank (Institute for Environmental Strategies, 2005)
"SPORT stands for “Strategic Partnership on REACH Testing”. The project was based on equal participation and joint management by the three strategic partners, i.e. the European Commission, the Member States and industry, including small and medium enterprises as well as Downstream Users, who all together formed the SPORT Steering Group. SPORT is a ground-breaking strategic partnership for testing proposed legislation at Community level and could serve as a blueprint for the future.